Characterizing primary human microglia: A comparative study with myeloid subsets and culture models - Melief, J.; Sneeboer, M. A. M.; Litjens, M.; Ormel, P. R.; Palmen, S. J. M. C.; Huitinga, I.; Kahn, R. S.; Hol, E. M.; de Witte, L. D. (Glia, 2016)
The biology of microglia has become subject to intense study, as they are widely recognized as crucial determinants of normal and pathologic brain functioning. While they are well studied in animal models, it is still strongly debated what specifies most accurately the phenotype and functioning of microglia in the human brain. In this study, we therefore isolated microglia from postmortem human brain tissue of corpus callosum (CC) and frontal cortex (CTX). The cells were phenotyped for a panel of typical microglia markers and genes involved in myeloid cell biology. Furthermore, their response to pro‐ and anti‐inflammatory stimuli was assessed. The microglia were compared to key human myeloid cell subsets, including monocytes, monocyte‐derived macrophages and monocyte‐derived dendritic cells, and several commonly used microglial cell models. Protein and mRNA expression profiles partly differed between microglia isolated from CC and frontal cortex and were clearly distinct from other myeloid subsets. Microglia responded to both pro‐ (LPS or poly I:C) and anti‐inflammatory (IL‐4 or dexamethasone) stimuli. Interestingly, pro‐inflammatory responses differed between microglia and monocyte‐derived macrophages, as the former responded more strongly to poly I:C and the latter more strongly to LPS. Furthermore, we defined a large phenotypic discrepancy between primary human microglia and currently used microglial cell models and cell lines. In conclusion, we further delineated the unique and specific features that discriminate human microglia from other myeloid subsets, and we show that currently used cellular models only partly reflect the phenotype of primary human microglia. GLIA 2016;64:1857–1868 Main Points Expression profiles differ between microglia and other myeloid subsets Distinct microglial responses to pro‐ and anti‐inflammatory stimuli Phenotypic discrepancy between microglia and currently used microglial cell models and cell lines